Murder at the Elms - Maxwell, Alyssa (Maxwell, Alyssa. Gilded Newport mystery, 2023)
"1901: Back from their honeymoon in Italy, Emma and Derrick are adapting to married life as they return to their duties at their jointly owned newspaper, the Newport Messenger. The Elms, coal baron Edward Berwind's newly completed Bellevue Avenue estate, is newsworthy for two reasons: A modern mansion for the new century, it is one of the first homes in America to be wired for electricity with no backup power system, generated by coal from Berwind's own mines. And their servants--with a single exception--have all gone on strike to protest their working conditions. Summarily dismissing and replacing his staff with cool and callous efficiency, Berwind throws a grand party to showcase the marvels of his new "cottage." Emma and Derrick are invited to the fete, which culminates not only in a fabulous musicale but an unforeseen tragedy--a chambermaid is found dead in the coal tunnel. In short order, it is also discovered that a guest's diamond necklace is missing and a laborer has disappeared. Detective Jesse Whyte entreats Emma and Derrick to help with the investigation and determine whether the murdered maid and stolen necklace are connected. As the dark deeds cast a shadow over the blazing mansion, it's up to Emma to shine a light on the culprit ..." --